A Cu-based eutectic alloy and its preparation method and application

Through the gradient structure design of Cu-based metacrystal alloy and combined with the laser selection melting forming process, the shortcomings in the wear resistance and service life of the existing synchronizer ring materials are solved, and high-performance and low-cost synchronizer rings are achieved. Material.

CN118621177BActive Publication Date: 2024-12-27ZHEJIANG YOUPENG NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411087293.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-09
Publication Date
2024-12-27
Estimated Expiration
2044-08-09

AI Technical Summary

Technical Problem

Among the existing synchronizer gear ring materials, steel-based gear rings have high cost and insufficient matrix strength. The service life of copper alloy gear rings in high load or high wear environments is limited, making it difficult to meet the wear resistance and service life requirements of automotive transmissions.

Method used

Cu-based semicrystal alloy is used, and the surface layer contains Cu15.0~20.0%, Fe 25.0~40.0%, Co 13.0~18.0%, Cr 13.0~18.0%, Ni 2.0~7.0%, Mo 3.0~8.0%, the core layer contains Cu 65.0~90.0%, Fe 7.0~27.0%, Co 2.0~14.0%, Cr 2.0~14.0%, and a transition layer is set between the two, and a laser selection melting forming process is used to prepare. , forming a gradient structure with high hardness, high wear resistance and high strength.

Benefits of technology

It realizes high wear resistance, stable friction coefficient and high strength of synchronizer rings, extends service life and reduces production costs, and is suitable for synchronizer ring applications in automotive transmissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118621177B_ABST
    Figure CN118621177B_ABST
Patent Text Reader

Abstract

The present invention provides a Cu-based monotectic alloy and a preparation method and application thereof, which relates to the technical field of monotectic alloys and solves the problem of poor wear resistance of existing Cu-based monotectic alloys; the Cu-based monotectic alloy comprises: a surface layer, the surface layer comprises the following raw materials in mass percentage: Cu 15.0-20.0%, Fe 25.0-40.0%, Co 13.0-18.0%, Cr 13.0-18.0%, Ni 2.0-7.0%, Mo 3.0-8.0%; a core layer, the core layer comprises the following raw materials in mass percentage: Cu 65.0-90.0%, Fe 7.0-27.0%, Co 2.0-14.0%, Cr 2.0-14.0%; wherein the thickness ratio of the surface layer to the core layer is 1:1-5. The difference in element distribution between the core layer and the surface layer helps to form a gradient structure, which can more effectively disperse stress when subjected to wear, reduce the generation and expansion of cracks, and thus improve the wear resistance of the Cu-based monotectic alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of monotectic alloys, and in particular to a Cu-based monotectic alloy and a preparation method and application thereof. Background Art

[0002] In recent years, with the rapid development of the automobile industry, traffic congestion has become increasingly prominent, which not only affects the driving experience, but also aggravates the wear of automobile transmissions, especially the synchronizer ring, a key component. As the core component of the transmission, the performance of the synchronizer ring directly affects the smoothness of gear shifting and the service life of the transmission.

[0003] Among the existing materials, synchronizer gear rings are mainly divided into two categories: steel-based gear rings and copper alloy gear rings. The raw materials and production equipment of steel-based gear rings rely on imports, resulting in high production costs for steel-based gear rings; the base strength of copper alloy gear rings is insufficient, which affects their service life in high-load or high-wear environments. Summary of the invention

[0004] The present disclosure provides a Cu-based eutectic alloy and a preparation method and application thereof, so as to at least solve the above technical problems existing in the prior art.

[0005] According to a first aspect of the present disclosure, there is provided a Cu-based eutectic alloy, comprising:

[0006] A surface layer, the surface layer comprising the following raw materials in percentage by mass: Cu 15.0-20.0%, Fe 25.0-40.0%, Co 13.0-18.0%, Cr 13.0-18.0%, Ni 2.0-7.0%, Mo 3.0-8.0%;

[0007] A core layer, the core layer comprising the following raw materials in percentage by weight: Cu 65.0-90.0%, Fe 7.0-27.0%, Co2.0-14.0%, Cr 2.0-14.0%;

[0008] Wherein, the thickness ratio of the surface layer to the core layer is 1:1-5.

[0009] In one embodiment, at least one transition layer is provided between the surface layer and the core layer, wherein the transition layer comprises the following raw materials in percentage by weight:

[0010] Cu30.0~60.0%, Fe 15.0~35.0%, Co 10.0~15.0%, Cr 15.0~20.0%.

[0011] In one embodiment, the transition layer includes a first transition layer and a second transition layer, wherein the first transition layer is close to the surface layer, and the second transition layer is close to the core layer;

[0012] The thickness ratio of the first transition layer to the second transition layer is 1:0.5-1.5.

[0013] In one embodiment, the surface layer further includes 2.0-7.0% by mass of carbides, and the particle size of the carbides is 20-30 μm.

[0014] In one embodiment, the particle size of the raw materials of the surface layer, the core layer and the transition layer is 30-53 μm.

[0015] According to a second aspect of the present disclosure, a method for preparing a Cu-based eutectic alloy is provided, the method comprising:

[0016] Mixing the surface raw materials and performing mechanical alloying treatment to obtain a surface mixed powder with uniform particle size;

[0017] Mixing the core layer raw materials and performing mechanized alloying treatment to obtain a core layer mixed powder with uniform particle size;

[0018] The CAD model of the Cu-based eutectic alloy is sliced ​​into layers to determine the slice contour information;

[0019] The processed core layer mixed powder and surface layer mixed powder are evenly spread on the substrate layer by layer, and the laser selective melting forming trajectory generated according to the slice profile information is scanned layer by layer to obtain a Cu-based eutectic alloy.

[0020] In one embodiment, the method further comprises:

[0021] Mixing the transition layer raw materials and performing mechanized alloying treatment to obtain a transition layer mixed powder with uniform particle size;

[0022] The CAD model of the Cu-based eutectic alloy is sliced ​​into layers to determine the slice contour information;

[0023] The processed core layer mixed powder, transition layer mixed powder and surface layer mixed powder are evenly spread on the substrate layer by layer, and the laser selective melting forming trajectory generated according to the slice contour information is scanned layer by layer to obtain a Cu-based eutectic alloy.

[0024] In one embodiment, the process parameters of the laser selective melting include:

[0025] When preparing the core layer, the laser power is 180~220 W, the laser scanning speed is 500~1500 mm / s, the spot diameter is 40~80μm, and the overlap rate is 40~60%;

[0026] When preparing the surface layer, the laser power is 230~280 W, the laser scanning speed is 300~600 mm / s, the spot diameter is 40~80 μm, and the overlap rate is 40~60%.

[0027] In one embodiment, the process parameters of the laser selective melting further include:

[0028] When preparing the transition layer, the laser power is 200~220 W, the laser scanning speed is 500~1000 mm / s, the spot diameter is 40~80 μm, and the overlap rate is 40~60%.

[0029] According to a third aspect of the present disclosure, there is provided a use of a Cu-based eutectic alloy in a synchronizer gear ring.

[0030] The present invention provides a Cu-based monotectic alloy and its preparation method and application, wherein the Cu-based monotectic alloy includes a surface layer and a core layer, the surface layer includes Cu15.0~20.0%, Fe25.0~40.0%, Co13.0~18.0%, Cr13.0~18.0%, Ni2.0~7.0%, Mo3.0~8.0%; the core layer includes Cu65.0~90.0%, Fe7.0~27.0%, Co2.0~14.0%, Cr2.0~14.0%. The difference in element distribution between the core layer and the surface layer helps to form a gradient structure, which can more effectively disperse stress when subjected to wear, reduce the generation and expansion of cracks, and thus improve the wear resistance of the alloy. In addition, the optimized combination of the surface layer and the core layer produces a synergistic effect. The high hardness and high wear resistance of the surface layer resist external wear, while the high strength and high toughness of the core layer provide good support and protection. The cooperation between the two makes the Cu-based eutectic alloy perform well in wear resistance.

[0031] It should be understood that the content described in this section is not intended to identify the key or important features of the embodiments of the present disclosure, nor is it intended to limit the scope of the present disclosure. Other features of the present disclosure will become easily understood through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The above and other objects, features and advantages of the exemplary embodiments of the present disclosure will become readily understood by reading the detailed description below with reference to the accompanying drawings. In the accompanying drawings, several embodiments of the present disclosure are shown in an exemplary and non-limiting manner, in which:

[0033] In the drawings, the same or corresponding reference numerals represent the same or corresponding parts.

[0034] Figure 1 A schematic structural diagram of a Cu-based eutectic alloy according to an embodiment of the present disclosure is shown;

[0035] Figure 2 A schematic structural diagram of another Cu-based eutectic alloy according to an embodiment of the present disclosure is shown. DETAILED DESCRIPTION

[0036] In order to make the purpose, features, and advantages of the present disclosure more obvious and easy to understand, the technical solutions in the embodiments of the present disclosure will be clearly and completely described below in conjunction with the drawings in the embodiments of the present disclosure. Obviously, the described embodiments are only part of the embodiments of the present disclosure, not all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present disclosure.

[0037] As the core component of the transmission, the performance of the synchronizer gear ring directly affects the smoothness of the gear shift and the service life of the transmission. The synchronizer gear ring needs to have excellent wear resistance, stable friction coefficient and high strength. Existing steel-based gear rings such as steel-based resin gear rings, steel-based carbon gear rings, steel-based molybdenum-sprayed gear rings, powder metallurgy gear rings and precision stamping gear rings are widely used due to their high matrix strength, good friction and wear performance, and strong overload resistance. However, the raw materials and production equipment of steel-based gear rings rely on imports, resulting in high costs; and steel-based gear rings are also prone to ablation, which limits their application.

[0038] Copper-based gear rings, such as conical surface processed threads, copper-based molybdenum-sprayed gear rings, sintered bronze gear rings, etc., have the advantages of simple preparation process and low cost; however, their low matrix strength and weak friction and wear performance limit their application in synchronizer gear rings. In view of the problems existing in current synchronizer gear ring materials, the present disclosure provides a low-cost, high-performance gear ring material, namely, a Cu-based eutectic alloy.

[0039] The present disclosure provides a Cu-based eutectic alloy, such as Figure 1 The figure shows a schematic diagram of the cross-sectional structure of a Cu-based monotectic alloy, which includes:

[0040] A surface layer, the surface layer comprising the following raw materials in percentage by mass: Cu 15.0-20.0%, Fe 25.0-40.0%, Co 13.0-18.0%, Cr 13.0-18.0%, Ni 2.0-7.0%, Mo 3.0-8.0%;

[0041] A core layer, the core layer comprising the following raw materials in percentage by weight: Cu 65.0-90.0%, Fe 7.0-27.0%, Co2.0-14.0%, Cr 2.0-14.0%;

[0042] Wherein, the thickness ratio of the surface layer to the core layer is 1:1-5.

[0043] By adding a higher proportion of Fe, Co, and Cr metal elements to the surface layer, these elements can form a hard phase in the Cu-based monotectic alloy, improving the hardness and wear resistance of the alloy; and the Cr element can not only improve the hardness, but also enhance the corrosion resistance and oxidation resistance of the alloy. The addition of Ni and Mo further improves the performance of the Cu-based monotectic alloy through the alloying effect. The addition of Ni can improve the plasticity and toughness of the surface layer, while Mo can enhance the corrosion resistance and wear resistance, making the surface layer have higher hardness and wear resistance, and can resist the friction and wear during gear shifting.

[0044] The high content of Cu in the core layer ensures the overall electrical and thermal conductivity of the alloy. At the same time, the addition of other elements such as Fe, Co and Cr also improves the strength and corrosion resistance of the core layer, so that the core layer provides solid support for the surface layer while maintaining the basic properties of the alloy. During the shifting process, the synchronizer ring will experience frictional heat generation or under extreme driving conditions (such as high-speed driving, heavy load, etc.), the synchronizer ring will be subject to a high thermal load, so thermal conductivity is very important for the core layer of the synchronizer ring. The core layer material has good thermal conductivity and can quickly transfer heat to the surrounding environment, thereby avoiding local overheating and causing material performance degradation or damage. This is crucial to ensure the long-term stability and reliability of the synchronizer ring. In addition, for vehicles with electric drive or hybrid systems, electrical conductivity is also very important as the core material of the synchronizer ring. The synchronizer ring interacts with electrical components. The electrical conductivity of the core material can ensure the normal operation of the electrical system and avoid problems such as electromagnetic interference or short circuits.

[0045] In the above scheme, the difference in element distribution between the core layer and the surface layer helps to form a gradient structure, which can more effectively disperse stress when subjected to wear, reduce the generation and expansion of cracks, and thus improve the wear resistance of the alloy. In addition, the optimized combination of the surface layer and the core layer produces a synergistic effect. The high hardness and high wear resistance of the surface layer resist external wear, while the high strength and high toughness of the core layer provide good support and protection. The two work together to make the Cu-based eutectic alloy perform well in terms of wear resistance.

[0046] The particle size of the raw materials of the surface layer and the core layer is 30~53 μm. For example, the raw materials of the surface layer or the core layer are mixed and mixed in a planetary ball mill for 1~3 hours and then dried. The ball-to-material ratio is 15:1, the rotation speed is 200 rpm, and the mixed powder particle size is 30~53 μm. By refining these metal powders to the nanometer level and uniformly distributing them in the alloy matrix as a nano-reinforcement phase; the introduction of nanoparticles can refine the grains, hinder dislocation movement, and provide a strengthening effect at a finer scale.

[0047] In one example, in order to achieve a smooth transition from the surface layer to the core layer, the Cu-based eutectic alloy further includes a transition layer, such as Figure 2As shown, the transition layer is arranged between the surface layer and the core layer, and at least one transition layer is arranged, and the thickness ratio of the transition layer to the surface layer is 1:1~2. The transition layer includes the following raw materials in mass percentage: Cu 30.0~60.0%, Fe 15.0~35.0%, Co10.0~15.0%, Cr 15.0~20.0%, and the particle size of the raw materials is 30~53 μm.

[0048] By setting a transition layer between the surface layer and the core layer, the transition layer can form a stress buffer area between the surface layer and the core layer, which helps to reduce the stress concentration generated at the interface between the surface layer and the core layer, thereby avoiding or reducing the generation and expansion of cracks. In addition, the transition layer can improve the interface bonding state between the surface layer and the core layer, reducing the performance degradation and failure risk caused by poor interface bonding. This enhanced interface bonding force helps to improve the overall performance and service life of the Cu-based monotectic alloy.

[0049] In one example, the transition layer is provided with two layers, namely the first transition layer and the second transition layer, wherein the first transition layer is close to the surface layer, the second transition layer is close to the core layer, and the thickness ratio of the first transition layer to the second transition layer is 1:0.5~1.5. The first transition layer includes the following raw materials in mass percentage: Cu30.0~45.0%, Fe 25.0~35.0%, Co 10.0~15.0%, Cr 15.0~20.0%; the second transition layer includes the following raw materials in mass percentage: Cu45.0~60.0%, Fe 15.0~25.0%, Co 10.0~15.0%, Cr 15.0~20.0%. By providing multiple transition layers, the interface bonding state between the surface layer and the core layer can be improved.

[0050] In one example, the surface layer also includes 2.0-7.0% by mass of carbides, wherein the particle size of the carbides is 20-30 μm. Carbides such as TiC and WC are uniformly distributed in the Cu-based eutectic alloy and serve as a macroscopic reinforcement phase to provide additional strength and hardness.

[0051] The present disclosure also provides a method for preparing a Cu-based eutectic alloy, the method comprising:

[0052] Step S1, mixing surface raw materials and performing mechanical alloying treatment to obtain surface mixed powder with uniform particle size.

[0053] According to the mass percentage of the surface raw materials, Cu 15.0~20.0%, Fe 25.0~40.0%, Co 13.0~18.0%, Cr 13.0~18.0%, Ni 2.0~7.0%, Mo 3.0~8.0%, Cu, Fe, Co, Cr, Ni, Mo purity above 99.9 wt.%. After mixing these metal powders, they are mixed in a planetary ball mill for 1~3 h and then dried for use, wherein the ball-to-material ratio is 15:1, the rotation speed is 200 rmp, and the mixed powder particle size is 30~53 μm.

[0054] Step S2: mixing the core layer raw materials and performing mechanized alloying treatment to obtain a core layer mixed powder with uniform particle size.

[0055] According to the mass percentage of the core layer raw materials, Cu 65.0~90.0%, Fe 7.0~27.0%, Co 2.0~14.0%, Cr2.0~14.0%, Cu, Fe, Co, Cr purity 99.9 wt.% or more. After mixing these metal powders, they are mixed in a planetary ball mill for 1~3 hours and then dried for use. The ball-to-material ratio is 15:1, the rotation speed is 200 rmp, and the mixed powder particle size is 30~53 μm. It should be noted that there is no order between steps S1 and S2, and it is only necessary to mix the raw materials separately.

[0056] Step S3, slicing the CAD model of the Cu-based eutectic alloy into layers to determine the slice contour information.

[0057] The CAD model of the Cu-based eutectic alloy is designed, including the detailed design of the surface layer and the core layer, and then the CAD model is cut into a series of two-dimensional slices, each slice represents a level in the forming process, the slice contour information is determined, and a series of laser selective melting forming trajectories are generated according to the slice contour information. There is no order between step S3 and S1 and S2.

[0058] Step S4, evenly spreading the processed core layer mixed powder and surface layer mixed powder on the substrate layer by layer, and scanning layer by layer according to the laser selective melting forming trajectory generated by the slice profile information to obtain a Cu-based eutectic alloy.

[0059] The laser selective melting chamber is evacuated, the substrate is preheated to 200°C, and then the raw materials are laid from bottom to top according to the structure of the Cu-based monotectic alloy. First, the core layer mixed powder is evenly spread on the substrate, and scanned layer by layer according to the laser selective melting forming trajectory. Then, the surface layer mixed powder is laid layer by layer, and scanned layer by layer according to the laser selective melting forming trajectory, and finally accumulated layer by layer into a solid Cu-based monotectic alloy.

[0060] In one example, if the Cu-based monotectic alloy further includes a transition layer, the method for preparing the Cu-based monotectic alloy further includes:

[0061] The transition layer raw materials are mixed and subjected to mechanical alloying treatment to obtain a transition layer mixed powder with uniform particle size.

[0062] According to the mass percentage of the transition layer raw materials, Cu30.0~60.0%, Fe 15.0~35.0%, Co 10.0~15.0%, Cr 15.0~20.0%, Cu, Fe, Co, Cr purity above 99.9 wt.%. After mixing these metal powders, they are mixed in a planetary ball mill for 1~3 hours and then dried for use, wherein the ball-to-material ratio is 15:1, the rotation speed is 200 rmp, and the mixed powder particle size is 30~53 μm.

[0063] In one example, in step S4, the process parameters of the laser selective melting include:

[0064] When preparing the core layer, the laser power is 180~220 W, the laser scanning speed is 500~1500 mm / s, the spot diameter is 40~80μm, and the overlap rate is 40~60%.

[0065] The laser power in this range (180~220 W) makes the Cu-based alloy reach a molten state while maintaining a relatively stable molten pool temperature, which is conducive to the formation of a uniform and dense core structure. Lower power may not be enough to completely melt the material, while too high power may cause the molten pool to overheat, increasing the risk of pores and cracks. The scanning speed directly affects the cooling rate and solidification structure of the molten pool. A slower speed helps the molten pool to be fully mixed and homogenized, but it will increase the processing time; a faster speed may cause the molten pool to cool rapidly and form a fine-grained structure, but it may also increase the risk of unfusion and cracks. The spot diameter determines the energy density of the laser beam and the size of the molten pool. A spot diameter of less than 40μm can provide a higher energy density, which is conducive to local precision heating, but it will cause the molten pool to be too small and affect the interlayer bonding. A spot diameter greater than 80μm can cover a larger area, but it will reduce the energy density and affect the melting effect. An overlap rate of 40~60% can reduce interlayer defects and improve the strength and density of the overall structure.

[0066] When preparing the surface layer, the laser power is 230~280 W, the laser scanning speed is 300~600 mm / s, the spot diameter is 40~80 μm, and the overlap rate is 40~60%.

[0067] Compared with the core layer, the laser power of the surface layer is increased to 230-280 W, which helps to form a denser and harder structure on the surface layer to improve the wear resistance and corrosion resistance of the surface layer. The scanning speed is reduced to 300-600 mm / s to extend the cooling time of the molten pool, promote element diffusion and homogenization, and reduce surface defects.

[0068] The process parameters of laser selective melting also include: when preparing the transition layer, the laser power is 200~220 W, the laser scanning speed is 500~1000 mm / s, the spot diameter is 40~80 μm, and the overlap rate is 40~60%.

[0069] The transition layer is designed to relieve the stress concentration caused by the difference in material properties between the core layer and the surface layer. The laser power is 200~220 W, which is between the core layer and the surface layer, and the scanning speed is 500~1000 mm / s, which is also relatively slow, so as to achieve a gradual change in composition and structure in the transition layer, thereby improving the overall mechanical properties and stability.

[0070] By finely controlling various parameters in the laser selective melting process, the structure and properties of the core layer, surface layer and transition layer of the Cu-based eutectic alloy can be precisely controlled, thereby preparing high-performance and high-reliability alloy materials.

[0071] In one example, the method further includes heat treating the Cu-based monotectic alloy, wherein the heat treatment process parameters include a heat treatment temperature of 800-1000°C and a heat treatment time of 2-8 hours. The heat treatment is performed to eliminate residual stress, refine grains, improve microstructure and enhance performance.

[0072] The present disclosure is described in detail below in conjunction with specific embodiments.

[0073] Example 1

[0074] A Cu-based eutectic alloy has a size of 70 mm×20 mm×10 mm (length×width×height), and comprises a surface layer and a core layer, wherein the thickness (height) of the surface layer is 3 mm, and the thickness (height) of the core layer is 7 mm.

[0075] The surface layer includes the following raw materials in mass percentage: Cu 15.0%, Fe 40.0%, Co 15.0%, Cr 15.0%, Ni7.0%, Mo 8.0%;

[0076] The core layer includes the following raw materials in mass percentage: Cu 65.0%, Fe 20.0%, Co 7.5%, Cr 7.5%.

[0077] The preparation method of the Cu-based eutectic alloy comprises:

[0078] (1) Cu, Fe, Co, Cr, Ni and Mo powders with a purity of more than 99.9 wt.% are mixed and prepared, and the chemical composition thereof is: Cu 15.0%, Fe 40.0%, Co 15.0%, Cr 15.0%, Ni 7.0%, Mo 8.0%, to obtain a surface mixed raw material.

[0079] Cu, Fe, Co and Cr powders with a purity of more than 99.9 wt.% are mixed and formulated, and the chemical composition thereof is: Cu 65.0%, Fe 20.0%, Co 7.5%, Cr 7.5%, to obtain a core layer mixed raw material.

[0080] (2) The surface layer mixed raw materials and the core layer mixed raw materials were mixed in a planetary ball mill for 2 h and then dried for use to obtain surface layer mixed powder and core layer mixed powder respectively; the ball-to-material ratio was 15:1, the rotation speed was 200 rmp, and the particle size of the mixed powder was 30-53 μm.

[0081] (3) Slice the CAD model of the Cu-based eutectic alloy into layers and determine the slice contour information.

[0082] (4) The laser selective melting chamber is evacuated, the substrate is preheated to 200°C, and then the raw materials are laid from bottom to top according to the structure of the Cu-based eutectic alloy. First, the core layer mixed powder is evenly spread on the substrate, and scanned layer by layer according to the laser selective melting forming trajectory. Then, the surface layer mixed powder is laid layer by layer, and scanned layer by layer according to the laser selective melting forming trajectory, and finally accumulated layer by layer into a solid Cu-based eutectic alloy.

[0083] The specific process parameters for preparing the core layer are: laser power 200 W, laser scanning speed 500 mm / s, spot diameter 80 μm, and overlap rate 50%.

[0084] The specific process parameters for preparing the surface layer are: laser power 230 W, laser scanning speed 300 mm / s, spot diameter 80 μm, and overlap rate 50%.

[0085] Example 2

[0086] A Cu-based eutectic alloy has a size of 70 mm×20 mm×10 mm (length×width×height), and comprises a surface layer and a core layer, wherein the thickness (height) of the surface layer is 2 mm, and the thickness (height) of the core layer is 8 mm.

[0087] The surface layer includes the following raw materials in mass percentage: Cu 20.0%, Fe 35.0%, Co 18.0%, Cr 18.0%, Ni4.0%, Mo 5.0%;

[0088] The core layer includes the following raw materials in mass percentage: Cu 85.0%, Fe 10.0%, Co 2.5%, Cr 2.5%.

[0089] The preparation method of the Cu-based eutectic alloy comprises:

[0090] (1) Cu, Fe, Co, Cr, Ni and Mo powders with a purity of more than 99.9 wt.% are mixed and prepared, and the chemical composition thereof is: Cu 20.0%, Fe 35.0%, Co 18.0%, Cr 18.0%, Ni 4.0%, Mo 5.0%, to obtain a surface mixed raw material.

[0091] Cu, Fe, Co and Cr powders with a purity of more than 99.9 wt.% are mixed and formulated, and the chemical composition thereof is: Cu 85.0%, Fe 10.0%, Co 2.5%, Cr 2.5%, to obtain a core layer mixed raw material.

[0092] (2) The surface layer mixed raw materials and the core layer mixed raw materials were mixed in a planetary ball mill for 2 h and then dried for use to obtain surface layer mixed powder and core layer mixed powder respectively; the ball-to-material ratio was 15:1, the rotation speed was 200 rmp, and the particle size of the mixed powder was 30-53 μm.

[0093] (3) Slice the CAD model of the Cu-based eutectic alloy into layers and determine the slice contour information.

[0094] (4) The laser selective melting chamber is evacuated, the substrate is preheated to 200°C, and then the raw materials are laid from bottom to top according to the structure of the Cu-based eutectic alloy. First, the core layer mixed powder is evenly spread on the substrate, and scanned layer by layer according to the laser selective melting forming trajectory. Then, the surface layer mixed powder is laid layer by layer, and scanned layer by layer according to the laser selective melting forming trajectory, and finally accumulated layer by layer into a solid Cu-based eutectic alloy.

[0095] The specific process parameters for preparing the core layer are: laser power 200 W, laser scanning speed 750 mm / s, spot diameter 60 μm, and overlap rate 40%.

[0096] The specific process parameters for preparing the surface layer are: laser power 230 W, laser scanning speed 500 mm / s, spot diameter 60 μm, and overlap rate 60%.

[0097] Example 3

[0098] A Cu-based eutectic alloy has a size of 70 mm×20 mm×10 mm (length×width×height), including a surface layer, a core layer and a transition layer, wherein the thickness (height) of the surface layer is 2 mm, the thickness (height) of the transition layer is 2 mm, and the thickness (height) of the core layer is 6 mm.

[0099] The surface layer includes the following raw materials in mass percentage: Cu 18.0%, Fe 40.0%, Co 13.0%, Cr 15.0%, Ni7.0%, Mo 7.0%;

[0100] The transition layer includes the following raw materials in mass percentage: Cu 30.0%, Fe 35.0%, Co 15.0%, Cr 20.0%;

[0101] The core layer includes the following raw materials in mass percentage: Cu 70.0%, Fe 15.0%, Co 7%, and Cr 8%.

[0102] The preparation method of the Cu-based eutectic alloy comprises:

[0103] (1) Cu, Fe, Co, Cr, Ni and Mo powders with a purity of more than 99.9 wt.% are mixed and prepared, and the chemical composition thereof is: Cu 18.0%, Fe 40.0%, Co 13.0%, Cr 15.0%, Ni 7.0%, Mo 7.0%, to obtain a surface mixed raw material.

[0104] Cu, Fe, Co and Cr powders with a purity of more than 99.9 wt.% are mixed and formulated, and the chemical composition thereof is: Cu 30.0%, Fe 35.0%, Co 15.0%, Cr 20.0%, to obtain a transition layer mixed raw material.

[0105] Cu, Fe, Co and Cr powders with a purity of more than 99.9 wt.% are mixed and formulated, and the chemical composition thereof is: Cu 70.0%, Fe 15.0%, Co 7%, Cr 8%, to obtain a core layer mixed raw material.

[0106] (2) The surface layer mixed raw materials, transition layer mixed raw materials and core layer mixed raw materials were mixed in a planetary ball mill for 2 hours and then dried for use to obtain surface layer mixed powder, transition layer mixed powder and core layer mixed powder respectively; the ball-to-material ratio was 15:1, the rotation speed was 200 rmp, and the particle size of the mixed powder was 30~53 μm.

[0107] (3) Slice the CAD model of the Cu-based eutectic alloy into layers and determine the slice contour information.

[0108] (4) The laser selective melting chamber is evacuated, the substrate is preheated to 200°C, and then the raw materials are laid from bottom to top according to the structure of the Cu-based eutectic alloy. First, the core layer mixed powder is evenly spread on the substrate, and scanned layer by layer according to the laser selective melting forming trajectory. Then, the transition layer mixed powder and the surface layer mixed powder are laid layer by layer in sequence, and scanned layer by layer according to the laser selective melting forming trajectory, and finally accumulated layer by layer into a solid Cu-based eutectic alloy.

[0109] The specific process parameters for preparing the core layer are: laser power 180 W, laser scanning speed 1000 mm / s, spot diameter 40 μm, and overlap rate 40%.

[0110] The specific process parameters for preparing the transition layer are: laser power 200 W, laser scanning speed 750 mm / s, spot diameter 60 μm, and overlap rate 40%.

[0111] The specific process parameters for preparing the surface layer are: laser power 250 W, laser scanning speed 600 mm / s, spot diameter 60 μm, and overlap rate 60%.

[0112] Example 4

[0113] A Cu-based eutectic alloy has a size of 70 mm×20 mm×10 mm (length×width×height), including a surface layer, a core layer and a transition layer, wherein the thickness (height) of the surface layer is 3 mm, the thickness (height) of the transition layer is 2 mm (the first transition layer and the second transition layer are 1 mm respectively), and the thickness (height) of the core layer is 5 mm.

[0114] The surface layer includes the following raw materials in mass percentage: Cu 20.0%, Fe 38.0%, Co 14.0%, Cr 15.0%, Ni5.0%, Mo 4.0%, TiC 4.0%;

[0115] The first transition layer includes the following raw materials in mass percentage: Cu 40.0%, Fe 30.0%, Co 10.0%, Cr 20.0%;

[0116] The second transition layer includes the following raw materials in mass percentage: Cu 50.0%, Fe 25.0%, Co 10.0%, Cr15.0%;

[0117] The core layer includes the following raw materials in mass percentage: Cu 80.0%, Fe 10.0%, Co 5%, Cr 5%.

[0118] The preparation method of the Cu-based eutectic alloy comprises:

[0119] (1) Cu, Fe, Co, Cr, Ni and Mo powders with a purity of more than 99.9 wt.% and TiC are mixed into a powder having a chemical composition of Cu 20.0%, Fe 38.0%, Co 14.0%, Cr 15.0%, Ni 5.0%, Mo 4.0% and TiC 4.0%, to obtain a surface mixed raw material.

[0120] Cu, Fe, Co and Cr powders with a purity of more than 99.9 wt.% are mixed and formulated, and the chemical composition thereof is: Cu 40.0%, Fe 30.0%, Co 10.0%, Cr 20.0%, to obtain a first transition layer mixed raw material.

[0121] Cu, Fe, Co and Cr powders with a purity of more than 99.9 wt.% are mixed and formulated, and the chemical composition thereof is: Cu 50.0%, Fe 25.0%, Co 10.0%, Cr 15.0%, to obtain a second transition layer mixed raw material.

[0122] Cu, Fe, Co and Cr powders with a purity of more than 99.9 wt.% are mixed and formulated, and the chemical composition thereof is: Cu 80.0%, Fe 10.0%, Co 5%, Cr 5%, to obtain a core layer mixed raw material.

[0123] (2) The surface layer mixed raw materials, the first transition layer mixed raw materials, the second transition layer mixed raw materials and the core layer mixed raw materials were mixed in a planetary ball mill for 2 h and then dried for use to obtain surface layer mixed powder, first transition layer mixed powder, second transition layer mixed powder and core layer mixed powder respectively; the ball-to-material ratio was 15:1, the rotation speed was 200 rmp, and the particle size of the mixed powder was 30-53 μm.

[0124] (3) Slice the CAD model of the Cu-based eutectic alloy into layers and determine the slice contour information.

[0125] (4) The laser selective melting chamber is evacuated, the substrate is preheated to 200°C, and then the raw materials are laid from bottom to top according to the structure of the Cu-based eutectic alloy. First, the core layer mixed powder is evenly spread on the substrate and scanned layer by layer according to the laser selective melting forming trajectory. Then, the second transition layer mixed powder, the first transition layer mixed powder and the surface layer mixed powder are laid layer by layer in sequence, and scanned layer by layer according to the laser selective melting forming trajectory, and finally accumulated layer by layer into a solid Cu-based eutectic alloy.

[0126] The specific process parameters for preparing the core layer are: laser power 210 W, laser scanning speed 600 mm / s, spot diameter 40 μm, and overlap rate 40%.

[0127] The specific process parameters for preparing the first transition layer are: laser power 220 W, laser scanning speed 500 mm / s, spot diameter 60 μm, and overlap rate 40%.

[0128] The specific process parameters for preparing the second transition layer are: laser power 220 W, laser scanning speed 500 mm / s, spot diameter 60 μm, and overlap rate 40%.

[0129] The specific process parameters for preparing the surface layer are: laser power 260 W, laser scanning speed 350 mm / s, spot diameter 60 μm, and overlap rate 60%.

[0130] Performance Testing

[0131] The Cu-based eutectic alloys prepared in Examples 1-4 were tested for appearance, hardness, tensile strength, elongation, wear resistance and density.

[0132] (1) Appearance: observation under a microscope.

[0133] Microstructure observation is one of the important means in materials science research. Through metallographic microscope, the morphology, size, distribution of grains inside the material as well as defects such as pores and cracks can be observed. For Cu-based eutectic alloys, dense microstructure and absence of pores and cracks are one of the important manifestations of its excellent performance.

[0134] (2) Hardness: Vickers hardness test.

[0135] Hardness is a physical quantity that measures the material's ability to resist deformation due to local pressure. Under a load of 0.2kgf, a diamond-shaped indenter is used to press into the material surface, and the hardness value is calculated based on the diagonal length of the indentation.

[0136] (3) Tensile strength: tensile test using a universal material testing machine.

[0137] Tensile strength is the ratio of the maximum tensile force that a material can withstand during stretching to the original cross-sectional area of ​​the sample. During the test, the sample is placed on a universal material testing machine, and a gradually increasing tensile force is applied until the sample breaks. The maximum tensile force before breaking is recorded, and the tensile strength is calculated based on the original cross-sectional area of ​​the sample.

[0138] (4) Elongation: tensile test using a universal material testing machine.

[0139] Elongation is the percentage of increase in the length of the specimen during the stretching process, reflecting the plastic deformation capacity of the material. In the tensile test, in addition to recording the maximum tensile force before fracture, the length of the specimen after fracture is also measured and the elongation is calculated based on this.

[0140] (5) Wear resistance: tested by friction and wear testing machine.

[0141] Wear resistance is the ability of a material to resist wear. A friction and wear testing machine is used to conduct simulated wear tests, and the wear resistance of Cu-based eutectic alloys is evaluated by comparing the wear amount or wear rate between them under the same conditions.

[0142] (6) Density: density test.

[0143] Density is the tightness of the internal structure of a material, reflecting the defects of the material such as pores and cracks. The density test is obtained by measuring the ratio of the actual density of the material to the theoretical density.

[0144] The performance test results are shown in Table 1.

[0145] Table 1 Performance test results of Cu-based eutectic alloys prepared in Examples 1-4

[0146]

[0147] According to the test results in Table 1, the Cu-based eutectic alloy prepared in the embodiment has excellent performance in appearance, hardness, tensile strength, elongation, wear resistance and density. It can be used as a material for synchronizer gear rings and has broad application prospects in the automotive field.

[0148] It should be understood that the various forms of processes shown above can be used to reorder, add or delete steps. For example, the steps recorded in this disclosure can be executed in parallel, sequentially or in different orders, as long as the desired results of the technical solutions disclosed in this disclosure can be achieved, and this document does not limit this.

[0149] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present disclosure, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0150] The above is only a specific embodiment of the present disclosure, but the protection scope of the present disclosure is not limited thereto. Any person skilled in the art who is familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present disclosure, which should be included in the protection scope of the present disclosure. Therefore, the protection scope of the present disclosure should be based on the protection scope of the claims.

Claims

1. A Cu-based eutectic alloy, characterized in that: include: A surface layer, wherein the surface layer is composed of the following raw materials in percentage by mass: Cu 15.0-20.0%, Fe 25.0-40.0%, Co 13.0-18.0%, Cr 13.0-18.0%, Ni 2.0-7.0%, and Mo 3.0-8.0%; A core layer, wherein the core layer is composed of the following raw materials in percentage by weight: Cu 65.0-90.0%, Fe 7.0-27.0%, Co 2.0-14.0%, Cr 2.0-14.0%; Wherein, the thickness ratio of the surface layer to the core layer is 1:1-5.

2. The Cu-based monotectic alloy according to claim 1, characterized in that: At least one transition layer is provided between the surface layer and the core layer, wherein the transition layer comprises the following raw materials in percentage by weight: Cu30.0~60.0%, Fe 15.0~35.0%, Co 10.0~15.0%, Cr 15.0~20.0%.

3. The Cu-based monotectic alloy according to claim 2, characterized in that: The transition layer comprises a first transition layer and a second transition layer, wherein the first transition layer is close to the surface layer, and the second transition layer is close to the core layer; The thickness ratio of the first transition layer to the second transition layer is 1:0.5-1.

5.

4. The Cu-based monotectic alloy according to claim 1, characterized in that: The surface layer also includes 2.0-7.0% by mass of carbides, and the particle size of the carbides is 20-30 μm.

5. The Cu-based monotectic alloy according to claim 2, characterized in that: The particle size of the raw materials of the surface layer, the core layer and the transition layer is 30-53 μm.

6. The method for preparing a Cu-based monotectic alloy according to any one of claims 1 to 5, characterized in that: The method comprises: Mixing the surface raw materials and performing mechanical alloying treatment to obtain a surface mixed powder with uniform particle size; Mixing the core layer raw materials and performing mechanized alloying treatment to obtain a core layer mixed powder with uniform particle size; The CAD model of the Cu-based eutectic alloy is sliced ​​into layers to determine the slice contour information; The processed core layer mixed powder and surface layer mixed powder are evenly spread on the substrate layer by layer, and the laser selective melting forming trajectory generated according to the slice profile information is scanned layer by layer to obtain a Cu-based eutectic alloy.

7. The method according to claim 6, characterized in that The method further comprises: Mixing the transition layer raw materials and performing mechanized alloying treatment to obtain a transition layer mixed powder with uniform particle size; The CAD model of the Cu-based eutectic alloy is sliced ​​into layers to determine the slice contour information; The processed core layer mixed powder, transition layer mixed powder and surface layer mixed powder are evenly spread on the substrate layer by layer, and the laser selective melting forming trajectory generated according to the slice contour information is scanned layer by layer to obtain a Cu-based eutectic alloy.

8. The method according to claim 6, characterized in that The process parameters of the laser selective melting include: When preparing the core layer, the laser power is 180~220 W, the laser scanning speed is 500~1500 mm / s, the spot diameter is 40~80 μm, and the overlap rate is 40~60%; When preparing the surface layer, the laser power is 230~280 W, the laser scanning speed is 300~600 mm / s, the spot diameter is 40~80 μm, and the overlap rate is 40~60%.

9. The method according to claim 7, characterized in that: The process parameters of the laser selective melting also include: When preparing the transition layer, the laser power is 200~220 W, the laser scanning speed is 500~1000 mm / s, the spot diameter is 40~80 μm, and the overlap rate is 40~60%.

10. Use of the Cu-based eutectic alloy according to any one of claims 1 to 5 in a synchronizer gear ring.